Pengaruh Pelatihan Keterampilan Belajar Jarak Jauh dan Motivasi Belajar Terhadap Kemajuan Akademik Mahasiswa Universitas Terbuka di Kabupaten Cianjur - Sopian, Meili Sapri; Soemaryani, Imas; Hilmiana (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2022)
This research is based on a brief explanation of Indonesian Open University which is known as a pioneer of distance education, it has become the identity of UT which we often find its existence both throughout the country and abroad. The Distance Learning System offered by UT in its learning activities has become a spectacle for other universities, especially when Covid-19 hit. Based on the phenomenon of distance learning, many people have discussed. Behind the problems that occur such as anxiety and increased stress caused by distance learning. UT has a strategy to introduce its learning system through distance learning skills training designed to help students prepare skills and develop successful strategies needed by students to understand and grow confidence to face the challenges of distance learning. This study also aims to determine the effect of distance learning skills training and learning motivation partially and simultaneously on the academic progress of Open University Students in Cianjur Regency. This research method uses a survey method with a correlational quantitative approach with a sample population of 70 people who are active UT students who are participants in PKBJJ 2022. The data processing used is SPSS version 25. The results showed that distance learning skills training had a positive and significant effect on academic progress. Learning motivation has a positive and significant effect on academic progress. And training in distance learning skills and learning motivation has a positive and significant effect on academic progress.